Tomato (Lycopersicon esculentum Mill.) anatomical, physiological, biochemical and production responses to drought stress - A mini-review essay - Massimi, M. (International Journal of Horticultural Science, 2021)
The cultivated plant climate association in agricultural yields is getting expanded consideration with regards to changing climatic conditions. Abiotic stressors can lead to morpho-anatomical, physiological, and biochemical alterations in harvests, resulting in a significant loss of profit. A comprehension of ecological elements and their communication with physiological cycles is critical for improving agricultural practices. Drought stress is among the main natural factor affecting plant development, growth, and yield measures. Assessing the impact of environmental change and atmospheric variability on tomato crop output will require a thorough understanding of this stress element. The physiology, development, improvement, yield, and quality of the tomato crop are all affected by dry season stress. This mini-review essay presents the most prominent features about the effects of drought stress on tomato crop plant physiology and production, with specific highlighting for the complex relationship between drought stress, and nutrients uptake.